SOCIAL POLICY IN THE PUBLIC ADMINISTRATION SYSTEM: ENSURING EQUAL ACCESS TO SOCIAL SERVICES - Krusian, Roman (Public Management and Policy, 2025)
In the context of European integration, the harmonization of the constitutional principles of the rule of law with the law of the European Union (EU) is of great importance. The purpose of the article was to analyze the constitutional principles of the rule of law in the context of political, economic, and cultural rapprochement of Ukraine with the EU. The article examines the constitutional principles of the rule of law in the context of European integration, which include the principles of the rule of law, separation of powers, priority of human rights and freedoms, social justice, legal responsibility of the state to the citizen, and equality of all before the law. It was found that despite the formal compliance of the Constitution of Ukraine with European standards of the rule of law, in practice there are problems with the implementation of these principles, which is manifested in the low level of trust in the judiciary and the presence of corruption. Failure to achieve strategic goals in this area of management is associated with the low level of effectiveness of the implementation of measures within the framework of the developed public management strategies. It is proven that the harmonization of the constitutional principles of the rule of law in the context of European integration requires ensuring the practical implementation of legal norms, monitoring the achievement of goals and implementation of measures within the framework of relevant strategic documents. The comparative analysis of the constitutional principles of the rule of law has shown the general consistency of the basic principles of Ukraine and the EU regarding human rights, independence of the judiciary, however, it is emphasized that there is no need for further institutional strengthening of the public administration and judicial system to ensure their practical implementation. The conclusions establish that the harmonization of the constitutional principles of the rule of law in Ukraine should be aimed at ensuring a real effective mechanism for law enforcement, the rule of law, and increasing the level of efficiency, effectiveness and democracy of state institutions. Future research should be aimed at studying the impact of public management on the development of the constitutional principles of the rule of law in Ukraine.